Coronavirus Disease 2019 ICU Patients Have Higher-Than-Expected Acute Physiology and Chronic Health Evaluation–Adjusted Mortality and Length of Stay Than Viral Pneumonia ICU Patients. Issue 7 (2nd April 2021) - Higgins, Thomas L.; Stark, Maureen M.; Henson, Kathy N.; Freeseman-Freeman, Laura
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To compare Acute Physiology and Chronic Health Evaluation-IV–adjusted mortality and length of stay outcomes of adult ICU patients who tested positive for coronavirus disease 2019 with patients admitted to ICU with other viral pneumonias including a subgroup with viral pneumonia and concurrent acute respiratory distress syndrome (viral pneumonia-acute respiratory distress syndrome). DESIGN: Retrospective review of Acute Physiology and Chronic Health Evaluation data collected from routine clinical care. SETTING: Forty-three hospitals contributing coronavirus disease 2019 patient data between March 14, and June 17, 2020, and 132 hospitals in the United States contributing data on viral pneumonia patients to the Acute Physiology and Chronic Health Evaluation database between January 1, 2014, and December 31, 2019. PATIENTS AND MEASUREMENTS: One thousand four hundred ninety-one patients with diagnosis of coronavirus disease 2019 infection and 4, 200 patients with a primary ( n = 2, 544) or secondary ( n = 1, 656) admitting diagnosis of noncoronavirus disease viral pneumonia receiving ICU care. A subset of 202 viral pneumonia patients with concurrent acute respiratory distress syndrome was examined separately. INTERVENTIONS: None. MAIN RESULTS: Mean age was 63.4 for coronavirus disease ( p = 0.064) versus 64.1 for viral pneumonia. Acute Physiology and Chronic Health Evaluation-IV scores were similar at 56.7 and 55.0, respectively ( p = 0.060), but gender and ethnic distributions differed, as did Pao 2 to Fio 2 ratio and WBC count at admission. The hospital standardized mortality ratio (95% CI) was 1.52 (1.35–1.68) for coronavirus disease patients and 0.82 (0.75–0.90) for viral pneumonia patients. In the coronavirus disease group, ICU and hospital length of stay were 3.1 and 3.0 days longer than in viral pneumonia patients. Standardized ICU and hospital length of stay ratios were 1.13 and 1.46 in the coronavirus disease group versus 0.95 and 0.94 in viral pneumonia patients. Forty-seven percent of coronavirus disease patients received invasive or noninvasive ventilatory support on their first ICU day versus 65% with viral pneumonia. Ventilator days in survivors were longer in coronavirus disease (10.4 d) than in viral pneumonia (4.3 d) patients, except in the viral pneumonia-acute respiratory distress syndrome subgroup (10.2 d) CONCLUSIONS: Severity-adjusted mortality and length of stay are higher for coronavirus disease 2019 patients than for viral pneumonia patients admitted to ICU. Coronavirus disease patients also have longer time on ventilator and ICU length of stay, comparable with the subset of viral pneumonia patients with concurrent acute respiratory distress syndrome. Mortality and length of stay increase with age and higher scores in both populations, but observed to predicted mortality and length of stay are higher than expected with coronavirus disease patients across all severity of illness levels. These findings have implications for benchmarking ICU outcomes during the coronavirus disease 2019 pandemic.